Effect of vital dyes on retinal pigmented epithelial cell viability and apoptosis: implications for chromovitrectomy - Penha, Fernando M (Ophthalmologica, 2013)
PURPOSE: To investigate in vitro effect of vital dyes on toxicity and apoptosis in a human retinal pigment epithelial (RPE) cell line. METHODS: ARPE-19 cells were exposed to brilliant blue-BriB, evans blue-EB, bromophenol blue-BroB, indocyanine green-ICG, infracyanine green-IfCG, light green-LG, fast green-FG, indigo carmine-IC and congo red-CR. BSS was used as the control. Five different concentrations and two times were tested. Cell viability was determined by MTS assay and apoptosis by Bax expression on western blot. RESULTS: All dyes significantly reduced cell viability after 3 minutes of exposure at all concentrations (p<0.01), except for BriB that was safe at concentrations up to 0.25mg/mL and CR up to 0.05mg/mL, while LG was safe in all concentrations. Toxicity was higher after 30 minutes of exposure. Expression of Bax was upregulated after all dyes exposure, except BriB; ICG had the highest Bax expression (p<0.01). CONCLUSIONS: Overall the safest dye was BriB followed by LG, IfCG, FG, CR, IC, BroB, RB and ICG. ICG was toxic at all concentrations and exposure times tested. Moreover, BriB was the only dye that did not induce apoptosis in ARPE-19 cells.